The Influence of Work Motivation on Employee Performance at PT. Mitradana Putra Utama Finance Bandung - Firmansyah, Deida Aulia Putri; Gunawan, Wawan; Ginanjar, Yayat; Saputra, Indra Nugraha; Nurjanah, Ai Siti (Journal of Bussines Management Basic, 2024)
This research is entitled the influence of work motivation on employee performance at PT. Mitradana Putra Utama Finance Bandung. The problem with this company is the lack of optimization in improving employee performance. This research aims to determine the effect of work motivation on employee performance at PT. Mitradana Putra Utama Finance Bandung. So, to improve employee performance, namely by providing work motivation by the company to employees. This research uses quantitative methods with a survey approach, documentation, and data collection techniques using observation and questionnaire methods. The sampling technique in this research used Non- Probability Sampling. The number of samples used in this research was 32 respondents. Research data was analyzed through data normality assumption tests, simple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing (t test). The results of this research show that work motivation and employee performance at PT. Mitradana Putra Utama Finance Bandung has a very strong relationship. This is proven by the correlation coefficient obtained at 0.742. Furthermore, work motivation (X) greatly influences employee performance (Y). This is proven by the calculation results of the coefficient of determination which was obtained at 55%. And there is a positive influence between work motivation (X) and employee performance (Y) which is obtained from the results of hypothesis testing which shows a t_count value of 6.059 > t_table 1.697.